The Effect Of Performance And Competency Evaluation On Employee Performance Through Service Quality At The Investment Office, Dairi Regency One-Stop Integrated Employment Service - Debby Nur Malawati; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2025)
Employee performance is influenced by various factors, including Performance Evaluation provided by the organization. Effective supervision and proper Competence can increase Job Satisfaction, which further contributes to improved performance. This study aims to identify the influence of Performance Evaluation on Employee Performance by considering the role of Job Satisfaction as an intervening variable in the Investment Office, Dairi Regency One-Stop Integrated Employment Service. Data was obtained through a survey of employees with a quantitative approach and analyzed using the Partial Least Squares (PLS) method. The results of the analysis showed that Performance Evaluation had a positive and significant influence on Job Satisfaction, with T-Statistic values of 4.718 and 4.838, respectively, and a P-Value of 0.000. Job Satisfaction is proven to have a positive and significant influence on Employee Performance with a T-Statistic value of 9.799 and a P-Value of 0.000, emphasizing the importance of Job Satisfaction as a performance driving factor. The analysis of indirect influence shows that Performance Evaluation significantly affects Employee Performance through Job Satisfaction, with an influence coefficient of 0.384. These findings indicate that an increase in Performance Evaluation will be more effective in encouraging Employee Performance when facilitated by high Job Satisfaction. Advice is provided to institutions to improve access to technology and training, as well as evaluate existing Performance Evaluation strategies. Researchers are further encouraged to explore other intervening variables, such as organizational culture and psychological capital, in the context of performance improvement.